RESPIRATORY SYNCYTIAL VIRUS INFECTION IN CHILDREN: NEW RESEARCH - T.V. Kulichenko (Union of pediatricians of Russia, 2009)
In a broad range of respiratory viruses the respiratory syncytial (RS) virus has a special place due to the diversity and severity of clinical manifestations of the disease in infants it causes. RS infection remains thus far a major medical and social issue causing high prevalence, needs for hospitalizations and mortality in risk groups of children. The modern program for prevention and treatment of RS infection is not yet efficient enough, however, significant progress has been made over the past decade with a new class of medications that have emerged and provides reliable protection against severe forms of RS virus infection. The article provides an overview of priority areas in the study of this issue, including the analysis of risk factors for a severe course of RS virus infection, developments in the molecular diagnostics in virology, optimization of bronchiolitis treatment and prevention of severe forms and unfavorable RS infection outcomes.Key words: respiratory syncytial virus, respiratory infections, children, bronchiolitis, diagnostics, treatment, prognosis, preterm infants, bronchopulmonary dysplasia, pulmonary function.